Analisis Kebijakan Pemerintah dalam Investasi Asing dari Sudut Pandang Ekonomi Politik - Bintang Aryanisah; Mellyana Candra; Ni Luh Viya Anggun Cahyani; Fawwaz Ghufran (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This article discusses the Indonesian government’s policy on foreign investment, focusing on its impact on the national economy. The study adopts an economic-political approach to analyze the role of the state in regulating foreign capital flows, as well as how foreign investment policies can affect economic stability, job creation, and equitable development. Through case studies in the infrastructure and manufacturing sectors, this article identifies the challenges and obstacles in implementing these policies, including political instability, bureaucracy, and regional regulatory differences. The article provides policy recommendations to optimize the benefits of foreign investment without neglecting domestic interests, with a focus on inclusiveness and sustainable development.